O skoob e a legitimação de obras literárias - Soares, Thiago de Oliveira (2016)
This dissertation discourses about the relation between the literature and the user of a virtual social network and deepen the discussion on the influence of virtual tools in the relationship between readers and books. More specifically, this work approaches concept and objective of the Brazilian social networking sites focused on literature and their functionalities and consequences for their users. The objective was to verify if Skoob, the largest site of Brazilian social network focused on literature, can function as legitimizing instance of literary works. For this reason, grounded on quantitative and qualitative questionnaires applied to the users of the sites, the Skoobers, which revealed, among other aspects, their literary preferences, the process of choosing new readings and forms of consumption of the books, and based by the Sociology of Reading, theory that has as its study center the literary text reader, the work discussed about the process of legitimation of literary works and the participation of the Skoob user and reader in it. The research provided a current view on Skoob's relationship with the academic literary environment, which showed possible changes in the legitimation process of literary works and the influence of publishers, consequently of the market, on that system.